Changes in splenic volumes following stereotactic ablative radiotherapy (SABR) to adrenal tumors - Nicolas Giraud; Miguel A. Palacios; John R. van Sornsen de Koste; Antonio M. Marzo; Peter S.N. van Rossum; Famke L. Schneiders; Suresh Senan (Clinical and Translational Radiation Oncology, 2025)
Purpose: Splenic irradiation can result in life-threatening infections. Updated dose constraints have been recommended for patients undergoing chemoradiotherapy and conventional radiotherapy but splenic constraints were not specified in trials of stereotactic ablative radiotherapy (SABR). We studied splenic doses in patients undergoing SABR for adrenal metastases and late changes in splenic volume (SV). Material and Methods: Patients treated with breath-hold MR-guided SABR for adrenal metastases were identified from an Ethics-approved database. Splenic dose constraints were not routinely used. The spleen was delineated retrospectively on both breath-hold CT and MR-scans. Mean spleen dose (MSD) and relative V5-10-20-30Gy values were derived from the baseline plan. SV was measured on available follow-up CT scans at 6–12–24 months. Regression analyses were performed to assess SV changes in relation to splenic dose and other parameters. Results: SABR was delivered to 113 adrenal tumors mostly using 5 fractions (64 % of tumors), 3 fractions (19 %) or a single fraction (14 %). Systemic therapy was administered during or within 3 months preceding/after SABR in 51 % of patients. Left-sided tumors comprised 56 % of total, and baseline median MSD and V10Gy were 9.7 Gy (range 1.5–28.4 Gy) and 46.3 % (range 0–100 %), respectively. Corresponding values for right-sided adrenal plans were 1.5 Gy (0.2–5.9 Gy) and 0 % (0–6.2 %), respectively. In multivariable analysis, a higher MSD was significantly associated with left laterality (p < 0.001), higher prescription dose (p = 0.02), and larger GTV (p < 0.001). An MSD of > 10 Gy was observed in 28 patients (25 %). Among these, a greater than 20 % decrease in SV was found in 46 % of patients with available follow-up at 6 months (n = 59), 40 % at 12 months (n = 47) and 50 % at 24 months (n = 31). Conclusion: Substantial reductions in spleen volume occur in 40–50 % of patients treated with adrenal SABR with an MSD of >10 Gy. The clinical relevance of splenic atrophy merits further study.